Strategi Dinas Pendidikan Provinsi Sumatera Selatan dalam Menyukseskan Program Guru Penggerak - Yanfatturrahman Yanfatturrahman; Alhadi Yan Putra; Muhammad Fahmi (Mathematics Education Study Program, 2025)
This research aims to analyze the strategy of the South Sumatra Provincial Education Office in implementing the Driving Teacher Program, an initiative from the Ministry of Education and Culture of the Republic of Indonesia which aims to create teachers who are competitive, innovative, and capable of being a driving force in improving the quality of education. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews, observation and documentation. The research results show that the South Sumatra Provincial Education Office implemented several key strategies, including intensive training, continuous monitoring and evaluation, as well as providing financial and non-financial support to the teachers involved. Apart from that, collaboration with various parties, such as higher education institutions and the local education community, is also an important factor in supporting the success of this program. The obstacles faced include limited budget and human resources, as well as barriers to technological adaptation. This study concludes that the strategy implemented by the Education Department has shown positive results in implementing the Teacher Mobilization Program in South Sumatra, however, efforts are still needed to improve implementation efficiency and strengthening coordination between stakeholders.